Expression of pro-angiogenic growth factors VEGF, EGF and bFGF and their topographical relation to neovascularisation in prostate cancer - Trojan, Lutz; Thomas, Daniel; Knoll, Thomas; Grobholz, Rainer; Alken, Peter; Michel, Maurice Stephan (Urological research, 2004)
The aim of the study was to quantify the expression of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) in prostate cancer and adjacent non-tumorous tissue in a standardized experimental set-up and to evaluate the paracrine effects of three endothelial stimuli on neovascularisation. Immunohistochemical staining of prostate cancer (PCa) specimens for VEGF, bFGF, EGF and the endothelial marker CD31 was performed (n=56). Sections were analyzed for growth factor-positive cancer/epithelial cells as well as staining intensity in (I) malignant and (II) non-tumorous tissue. Within PCa the topographic relationship (TR) of maximum microvessel density (MWD) and maximum expression of each growth factor was assessed. The number of VEGF- and EGF-positive cells in PCa was significantly enhanced compared with non-tumorous tissue (p<0.0001), whereas there was no difference in staining intensity. In contrast, the staining intensity of bFGF sections revealed a stronger expression in non-tumorous tissue compared with PCa (p<0.0001). In benign glands, VEGF, EGF and bFGF expression is chiefly restricted to basal cells. VEGF and EGF displayed a close TR in 65 and 57% of cases, respectively, whereas bFGF revealed a close TR in only 43% of PCa specimens. The results outline the relationship of the investigated growth factors and angiogenesis in PCa, which is strongest for VEGF and EGF. The relevance of VEGF and EGF is underlined by the increased number of positive cancer cells. Although previously reported to be a pro-angiogenic growth hormone, bFGF appears to play an assimilably minor role in the angiogenesis of PCa.